2008
DOI: 10.1021/jp0766555
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Photophysics, Photoelectrical Properties, and Photoconductivity Relaxation Dynamics in the Case of Nanocrystalline Tin(II) Selenide Thin Films

Abstract: Charge-carrier transport properties in chemically deposited thin films composed of close-packed tin(II) selenide nanocrystals were studied both in the dark and under conditions when internal photoelectric effect is manifested in the nanostructured material. Stationary and time-resolved experiments were performed to characterize the photophysics of quantum-confined nanocrystals synthesized in thin film form. The charge-carrier transport through the films was found to occur predominantly by the thermionic emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 99 publications
1
48
1
1
Order By: Relevance
“…Notably, few‐layer SnSe FETs also show a large current ON/OFF ratio (≈2 × 10 7 ) and the highest anisotropic ratio in the mobility (≈5.8) among all the reported 2D anisotropic materials . These significant properties equip SnSe with great potential in various electronic and optoelectronic applications, including solar cells, infrared optoelectronic devices, radiation detectors, polarity‐dependent memory switching devices, artificial synaptic devices, and spin‐transport devices . Thus far, the exploration of anisotropic properties in 2D SnSe has focused on thermoelectric properties, first‐principles theoretical calculations, linear optical absorption, Raman scattering, and electrical transport characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, few‐layer SnSe FETs also show a large current ON/OFF ratio (≈2 × 10 7 ) and the highest anisotropic ratio in the mobility (≈5.8) among all the reported 2D anisotropic materials . These significant properties equip SnSe with great potential in various electronic and optoelectronic applications, including solar cells, infrared optoelectronic devices, radiation detectors, polarity‐dependent memory switching devices, artificial synaptic devices, and spin‐transport devices . Thus far, the exploration of anisotropic properties in 2D SnSe has focused on thermoelectric properties, first‐principles theoretical calculations, linear optical absorption, Raman scattering, and electrical transport characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…SnSe is of interest for a wide range of potential applications such as for memory switching devices [2,3], infrared optoelectronic devices [4,5], solar cells [6,7] and anode materials for rechargeable lithium batteries [8]. Zhao et al [1] recently reported that single-crystal SnSe exhibited a low thermal conductivity above room temperature resulting in a high thermoelectric figure of merit, ZT, of 2.6 at 923 K along the b-axis (ZT ¼S 2 σT/κ where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity and T is the absolute temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, motivated by its narrow band gap, layered structure and some other advantages, including natural abundance, low toxicity and chemical stability, research interests in SnSe nanomaterial have been dramatically growing. Various SnSe nanostructures, including thin films [14,16], nanocrystals [17], and layered nanosheets [18], have been investigated. However, very few works on the synthesis of one-dimensional (1D) SnSe nanostructure arrays have been reported, and all of them adopt the chemical solution method [15,16].…”
Section: Introductionmentioning
confidence: 99%